Effect of different substrates on the growth of jacarezinho pumpkin seedlings - Ribeiro, Luis Felipe Oliveira; Cardozo Neto, Antônio; Borchardt, Breno Benincá; Bonatto, Amanda Parmagnani; Silva, Francine Bonomo Crispim; Ribeiro, João Victor Oliveira; Altoé, Jalille Amim (Brazilian Journal of Production Engineering, 2024)
In cucurbits, seedling preparation is one of the factors that affects the vegetative and reproductive quality of plants, considered one of the most explensive practices in the cultivation system, making it essential to search for alternative substrates in order to reduce initial production costs. The objective of this work was to evaluate the effect of different substrates on the growth of jacarezinho pumpkin using commercial and organic substrates. The design used was completely randomized, with seven replications. Four treatments were used, described as: T1 = Bioplant Plus®, T2 = Gully soil + Provaso® (1:1), T3 = Gully soil + cattle manure (1:1) and T4 = Gully soil + manure chicken (1:1). The results showed that the ravine soil + cattle manure and ravine soil + Provaso® presented the same statistical equality as the commercial substrate Bioplant Plus® in all analyzed variables, with the ravine soil + bovine manure (1:1) presenting the best growth of pumpkin plants with adequate average values ​​in all variables, including total dry matter.